Research on the Electromagnetic Interference of Yanmenguan DC Grounding Electrode on West-East Transmission Gas Pipeline. Issue 1 (February 2021) - Shi, Weiguang; Wang, Kesheng; Liu, Wei; Li, Pingwei; Cai, Xinjing
Abstract: There was a west-east gas transmission pipeline nearby the Yanmenguan DC grounding electrode. In order to assess the electromagnetic interference of Yanmenguan DC grounding electrode on the pipeline, an electromagnetic simulation model was established. The pipeline to earth potential was analyzed. The effects of insulation layers and insulation joints on the pipeline to earth potential were investigated. It can provide theorical support for the pratical operation of gas pipelines.